Income-based inequality of adolescent obesity in Australia - James, Adrian; Mendolia, Silvia; Paloyo, Alfredo R (My University, 2021)
We investigate the magnitude and drivers of income-based inequality of adolescent obesity. Using the Household, Income and Labour Dynamics in Australia survey, we estimate a concentration index of –0.1225. We also demonstrate that the inequality doubled between the years 2006 and 2014. In a decomposition analysis, we show that the greatest contributors to the observed inequality in adolescent obesity rates are socioeconomic status and maternal obesity status.
Economic Letters
Keywords: Disadvantage, adversity and resilience; Health and wellbeing